Incidência e fatores de risco para infecções de sítio cirúrgico ortopédicas com uso de prótese: coorte não concorrente - Renata Cristina Gonçalves Cunha (2019)
Orthopedic surgeries with prosthesis are procedures used for the treatment of diseases in joints. Although it is a widely used procedure, the patient is subject to various complications and treatment failure. Among these complications, surgical site infection (SSI) is one of the most common, with incidence varying between 1.4% and 12.6%. To prevent this condition, monitoring incidence and monitoring risk factors will allow adoptions of evidencebased prevention practices for safer care. This study is a non-concurrent cohort of 149 patients undergoing total hip arthroplasty (THA) and total knee arthroplasty (TKA). The general objective was to analyze the epidemiological aspects of surgical site infections in patients submitted to orthopedic surgery from 2015 to 2018 at a large hospital in Belo Horizonte, Minas Gerais. The specific objectives were to estimate the incidence of surgical site infections; to estimate the incidence of surgical site infection (SSI) by topography; identify the risk factors associated with orthopedic infection; identify the microorganisms responsible for infections and propose a multivariate predictive model. In the univariate analysis, the nonparametric Mann Whitney test was applied. And to verify the hypothesis of association between the categorical variables with the groups, Fisher's exact test was applied. In the multivariate analysis, the Logistic Regression model was applied (p-value <0.05). Six SSIs were reported, with an overall rate of 4.03%, all characterized as superficial. In patients who underwent TKA, the incidence of SSI was 2.94% and those who undergoing TKA, 4.94%. The risk factors identified for orthopedic SSIs were age and systemic arterial hypertension. The isolated microorganisms were Enterobacter cloacae, Acinetobacter baumannii and Stenotrophomonas maltophilia. The SSI rates found in this study were higher than those recommended by the NHSN / CDC.